Impacts of the 2004 tsunami: preparedness of the Malaysian coastal communities - Zahari, Rustam Khairi; Raja Ariffin, Raja Noriza; Asmawi, M. Zainora; Ibrahim, Aisyah Nadrah (Elsevier, 2013)
The Indian Ocean tsunami of 26th December 2004 unleashed catastrophe in many nations including coastal communities located along the west-coast of Malaysian Peninsular. The goal of this study is to explore the impact of the tsunami to the preparedness of the affected coastal communities. Data was collected through questionnaire, interviews, documents analysis and field observations. It was found that the 2004 tsunami disaster has left a significant mark on Malaysia's and the world's disaster management landscape but the tragedy has also heightened disaster awareness and steps must be taken to ensure vulnerable communities are well-equipped to face any eventualities.